Behaviours Of Fiber Concrete Mechanic Using Polypropylene - Nur Alfikri; Alex Kurniawandy; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This research studies the mechanical properties of polypropylene concrete such as compressive strength, modulus of elasticity, splitting tensile strength, flexural strength and ultrasonic pulse velocity (UPV). Application of polypropylene fiber aims to improve the mechanical properties of normal concrete. The specimens were cylinder and beam shapes. The variations of polypropylene fiber used were 0,0 kg/m3, 1,2 kg/m3, 1,4 kg/m3, 1,6 kg/m3, 1,8 kg/m3 and 2,0 kg/m3. The result of research shows the highest compressive strength, modulus of elasticity, flexural strength and UPV occurred at 1,4 kg/m3 addition of polypropylene whereas. The highest splitting tensile strength was occured at 2,0 kg/m3 polypropylene fiber addition. According to the result, additional polypropylene fiber can improve the mechanical properties of concrete, especially compressive strength, modulus ofelasticity, splitting tensile strength and UPV of concrete.Keyword : polypropylene fiber, mechanical properties, compressive strength, splitting tensile strength, UPV